2013
DOI: 10.1155/2013/907016
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Qingpeng Ointment in Atopic Dermatitis-Like Murine Model

Abstract: Qingpeng ointment (QP) is a Chinese medicine which has been used in treatment of atopic dermatitis (AD) in China. AD-like lesions were induced in BALB/c mice by repeated application of 2,4-dinitrofluorobenzene (DNFB) on shaved backs. The mice were then treated for 2 weeks with QP of different concentrations and Mometasone Furoate cream (MF), respectively. Macroscopic and microscopic changes of the skin lesions were observed after the treatment. The levels of serum immunoglobulin (Ig) E, tissue interferon (IFN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…AD is a complex allergic condition that is characterized by high IgE levels, and IgE-mediated mechanisms are thought to play an important role in the pathogenesis of this disease [ 1 ]. In the present study, we applied DNFB as a hapten to BALB/c mice for 5 weeks to induce dermatitis, with an immune profile of higher levels of IgE, which was similar to the early reaction of AD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AD is a complex allergic condition that is characterized by high IgE levels, and IgE-mediated mechanisms are thought to play an important role in the pathogenesis of this disease [ 1 ]. In the present study, we applied DNFB as a hapten to BALB/c mice for 5 weeks to induce dermatitis, with an immune profile of higher levels of IgE, which was similar to the early reaction of AD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BALB/c mice were divided into two groups, namely the AD group (n = 10) and the control group (n = 10). DNFB (Wako, Japan) diluted in the mixture of acetone and olive oil (4:1) was used for sensitization [ 29 ]. The dorsal side of the mice was shaved on the first week of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This staining allows observing both rodent and human connective tissues; purple colored, metachromatic staining reactive cells are observed and evaluated (Lee et al, 2006). It was previously demonstrated that decreased in numbers of mast cells might be due to efficacy of therapeutic agents (Ahn et al, 2009;Nagai & Okunishi, 2009;Li et al, 2010;Zheng et al, 2011;Li et al, 2013). As we demonstrated, PTC significantly lowered the numbers of mast cells in mice dorsal skin, suggesting its suppressing potential against AD like symptoms and providing a possibility to utilize PTN as a raw material for the development of therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of AD by using DNFB was established based on previous research ( Li et al, 2013 ). DNFB was purchased from Sigma Chemical (St. Louis, MO, USA) and dissolved in a mixture of acetone and olive oil (4:1).…”
Section: Methodsmentioning
confidence: 99%